Adsorption of methylene blue using green pea peels (Pisum sativum): a cost-effective option for dye-based wastewater treatment - Dod, Ramesh; Banerjee, Goutam; Saini, S. (Biotechnology and Bioprocess Engineering, 2012)
Methylene blue (MB), a common toxic dye, is largely discharged from dyeing processes for acrylic, nylon, silk, and woolen fabrics in textile industries. While application of conventional removal processes like chemical precipitation, ion exchange, commercial activated carbon adsorption, etc often become cost-prohibitive, the adsorption of MB by abundantly available green pea peel (GPP: Pisum sativum) derived and acid-treated carbon (GPP-AC) has proved to be a cost-attractive option in the present study. The physicochemical and morphological characteristics of GPP-AC were examined with the help of XRD, BET surface area, SEM, and Fourier transform infrared spectrophotometry ((FT-IR) analysis. The influences of such adsorption parameters as initial dye concentration, pH, contact time, adsorbent dosage, agitation speed, particle size, and temperature were evaluated and optimized. The equilibrium contact time for maximum adsorption of MB on to GPPAC was found to be 7 h. The equilibrium data of the adsorption process were modeled by using the Langmuir, Freundlich, Temkin, and Dubinin-Raduskevich (D-R) isotherms. However, the adsorption equilibrium data were best described by the Langmuir Isotherm model, with a maximum adsorption capacity of 163.94 mg MB/g GPPAC at 30A degrees C.
Keywords: Adsorption; Dubinin-raduskevich; Freundlich; green peas peels; Isotherms; Langmuir; Methylene blue; Temkin

Removal of methylene blue (MB) dye from water environment by processed Jowar Stalk [Sorghum bicolor (L.) Moench] adsorbent - Dod, Ramesh; Banerjee, Goutam; Saini, D. R. (Clean Technologies and Environmental Policy, 2015)
The present paper discusses the results of the study of adsorption of methylene blue on activated carbon, derived from cheap and abundantly available agro-residue of Jowar Stalk (JS) [Sorghum bicolor (L.) Moench] on suitable heat and acid treatment. The physico-chemical and morphological characteristics of processed carbon of JS origin were studied using X-ray diffraction, scanning electron microscopy, Brunauer, Emmett and Teller surface area, and Fourier transform infrared spectrophotometry analyses. The batch studies revealed optimum values of adsorption parameters such as pH, adsorbent dosage, agitation speed, grain size, temperature, and contact time as 7, 1.5 g l(-1), 200 rpm, finer than 75 A mu m, 30 A degrees C, and 7 h, respectively. The adsorption isotherm data were best described by Langmuir isotherm model with a maximum adsorption capacity of 176.05 mg MB g(-1) JS activated carbon at 30 A degrees C, which is higher than that available with adsorbents used by past researchers. In terms of cost-effectiveness, JS carbon shows its superiority over commercially available carbon.
Keywords: Adsorption; Isotherms; kinetics; Methylene blue; Processed Jowar Stalk [Sorghum bicolor (L.) Moench]